Recent developments in linguistics in areas of national periphery (Santa Cruz, 1983-2016): agents, agentivity and language bodies - Gasel, Alejandro Fabián (2023)
This article develops an analysis of the process of institutionalisation of Linguistics in higher education in the province of Santa Cruz, Argentina, during the period 1983-2016. We study the teaching function (institutional programmes and minimum contents such as the subjects Discourse Analysis and Production and Academic Literacy) and the research function (history of the agents and of a project based at the National University of Southern Patagonia), in whose analysis we question the trajectories and links between different agents in order to think about their impact on the consolidation of Linguistics in the periphery of Santa Cruz and at national level. To do so, we appeal to theoretical and methodological tools from the fields of glotopolitics (Narvaja de Arnoux, 2016; Del Valle, 2016), institutionalisation (Gerbaudo, 2014; Sapiro, 2013) and discourse analysis from a materialist perspective (Glozman and Monteiro, 2010). We argue that in the period studied the institutionalisation of the linguistic discipline in Santa Cruz underwent a process of expansion characterised by the consolidation of the functions teaching and research and by a strong state presence, resulting in a linguistics with local actors that depend on the state.